PERUBAHAN DAN PERKEMBANGAN MODEL PESANTREN - Abdul Malik Karim Amrullah (el-hikmah, 2011)
Pesantren has been intsitution that is survive up to the present. Nowdays pesantren became one of institutions which adapted and changed for a dynamic social change. Pesantren is the model for enhancing educational character that stated by Indonesian ministre of education Muh. Nuh. Its caused of the special characters that continously kept since formerly such as teacher’s obidience, the consistency of learning model, the concept of barakah and so on. The globalization era is also contributing an oportunity a number of non formal educational institution to arange and change the system management of pesantren. A research about management of pesantren states that it changes but pesantren still commitment to keep the traditional maners.